2019
DOI: 10.1002/gps.5243
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social isolation and cognitive functioning. Longitudinal findings based on the German Ageing Survey

Abstract: Objectives: There is a lack of longitudinal studies, which are both based on nationally representative samples and use standardized instruments to quantify social isolation.Thus, the purpose of this study was to determine the link between perceived social isolation and cognitive functioning longitudinally.Methods/Design: Longitudinal data with n = 6420 from 2014 (wave 5) to 2017 (wave 6) were drawn from the German Ageing Survey (nationally representative sample of individuals aged 40 years and over). Perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…between risk factors and cognitive decline and try to establish directional relationships (e.g., Boss et al, 2015). Follow-up periods for all 12 longitudinal studies ranged from 3 (Zhou et al, 2019;Hajek et al, 2020) to 11 years (Luchetti et al, 2020). All studies reported findings from participants enrolled in large, population-based studies, being these the Survey of Health, Ageing and Retirement in Europe (SHARE; Luchetti et al, 2020), the English Longitudinal Study of Ageing (ELSA; Yin et al, 2019;Read et al, 2020), the Cognitive Function and Ageing Study-Wales (CFAS-Wales; Evans et al, 2018), the Cambridge City over-75s Cohort Study (CC75C; Wang et al, 2020), the Irish Longitudinal Study of Ageing (TILDA;McHugh Power et al, 2019, 2020, the Collaborative Research on Ageing in Europe study in Europe (COURAGE; Lara et al, 2019), the Health and Retirement Study (HRS; Griffin et al, 2020), the Chinese Longitudinal Healthy Longevity Survey (CLHLS; Zhou et al, 2019), the China Health and Retirement Longitudinal Study (CHARLS; Yu et al, 2020) and the German Ageing Survey (DEAS; Hajek et al, 2020).…”
Section: Study Characteristics Designmentioning
confidence: 99%
“…between risk factors and cognitive decline and try to establish directional relationships (e.g., Boss et al, 2015). Follow-up periods for all 12 longitudinal studies ranged from 3 (Zhou et al, 2019;Hajek et al, 2020) to 11 years (Luchetti et al, 2020). All studies reported findings from participants enrolled in large, population-based studies, being these the Survey of Health, Ageing and Retirement in Europe (SHARE; Luchetti et al, 2020), the English Longitudinal Study of Ageing (ELSA; Yin et al, 2019;Read et al, 2020), the Cognitive Function and Ageing Study-Wales (CFAS-Wales; Evans et al, 2018), the Cambridge City over-75s Cohort Study (CC75C; Wang et al, 2020), the Irish Longitudinal Study of Ageing (TILDA;McHugh Power et al, 2019, 2020, the Collaborative Research on Ageing in Europe study in Europe (COURAGE; Lara et al, 2019), the Health and Retirement Study (HRS; Griffin et al, 2020), the Chinese Longitudinal Healthy Longevity Survey (CLHLS; Zhou et al, 2019), the China Health and Retirement Longitudinal Study (CHARLS; Yu et al, 2020) and the German Ageing Survey (DEAS; Hajek et al, 2020).…”
Section: Study Characteristics Designmentioning
confidence: 99%
“…In total, authors from 16 selected articles examined the association between functional aspects of social relationships and cognitive decline [ 16 , 38 , 39 , 42 , 43 , 45 , 47 , 58 66 ]. Aspects included: social support (i.e., the availability of sources of material or emotional help, 12 articles), loneliness or isolation (i.e., subjective perception of loneliness or depression, 10 articles).…”
Section: Resultsmentioning
confidence: 99%
“…Failure to address loneliness in older adults could profoundly impact the healthcare system. Social isolation and loneliness in older adults have been associated with incidence and progression of cardiovascular disease (Banerjee et al, 2014), cognitive decline (Hajek et al, 2020), Alzheimer's disease (Wilson et al, 2007), and impaired cellular immunity (Hawkley & Cacioppo, 2010). Zhang et al (2018) described the correlation between perceived social isolation and medical service utilization in older adults as demonstrated by more frequent primary care visits, whereas Mistry et al (2001) found that 1-year rehospitalization rates were four to fi ve times higher than in low-isolation risk patients.…”
Section: Significance Of the Problemmentioning
confidence: 99%